2018
DOI: 10.1080/13218719.2018.1504242
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Risk of Australian Indigenous Sexual Offenders Reoffending: A Review of the Research Literature and Court Decisions

Abstract: The assessment of offenders' risk of reoffending, particularly sexual reoffending, is a core activity of forensic mental health practitioners. The purpose of these assessments is to reduce the risk of harm to the public, but they are controversial and become more contentious when Australian practitioners who want to undertake such assessments in an ethically responsible way must use reliable validated instruments, disclose the limitations of their assessment methods, instruments and data to judicial decision-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…Decision-makers in the justice system routinely make sentencing, intervention and discharge decisions in respect of sexual offenders (Allan et al, 2006). These decisions impact on offenders’ interests and legal rights and, indirectly, the interests of members of the community, especially those in the communities where the relevant offences took place (Allan et al, 2018). Decision-makers must in all these cases consider the likelihood that offenders will reoffend, and they frequently rely on mental health evaluators’ assessments of offenders’ risk of reoffending.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Decision-makers in the justice system routinely make sentencing, intervention and discharge decisions in respect of sexual offenders (Allan et al, 2006). These decisions impact on offenders’ interests and legal rights and, indirectly, the interests of members of the community, especially those in the communities where the relevant offences took place (Allan et al, 2018). Decision-makers must in all these cases consider the likelihood that offenders will reoffend, and they frequently rely on mental health evaluators’ assessments of offenders’ risk of reoffending.…”
mentioning
confidence: 99%
“…Allan et al (2018) found that Australian evaluators who assess sexual offenders from Aboriginal and Torres Strait Island or Indigenous communities use a range of available assessment instruments. The development of these risk assessment instruments can be traced back to the finding in Baxstrom v Herold (1966) that clinical judgments of the risk of reoffending were not better than chance (Hunt & Wiley, 1968; Steadman, 1973, 1980).…”
mentioning
confidence: 99%
See 3 more Smart Citations